Presence of Unabsorbed Free Amino Acids at the End of the Small Intestine of Humans and Pigs: Potential Implications for Amino Acid Bioavailability. (7th June 2021) - van der Wielen, Nikkie; de Vries, Sonja; Gerrits, Walter; Jannink, Kim; Moughan, Paul; Mensink, Marco; Hendriks, Wouter
Abstract: Objectives: The protein quality digestible indispensable amino acid scores (DIAAS) require determination of amino acid (AA) bioavailability, which is often quantified as the net disappearance of dietary AAs at the end of the small intestine, so-called true ileal digestibility. It is often assumed that bioavailability is mainly influenced by protein breakdown and that free AAs are completely absorbed by the small intestine. However, some studies report substantial amounts of free AAs in the unabsorbed protein fraction present in terminal ileal digesta. This study quantified free AAs in ileal digesta of humans and pigs and estimated their impact on AA bioavailability. Methods: Two studies were performed with 3 diets, i.e., zein, whey or protein-free. In study 1, ileal digesta of 8 human ileostomates was collected over 9 hours after ingestion of a single meal. In study 2, 12 pigs were fed 7 days with one of the 3 diets and ileal digesta was collected over 9 h on the last 2 days according to a standardized digestibility protocol. Total and free AA content were analyzed in ileal digesta. Results: All ileal digesta contained free AAs. If the analyzed free AAs would have been absorbed in the small intestine the bioavailability for whey, which was > 95%, would only increase 0.4%-unit on average for the different AAs in humans and 0.1%-unit in pigs. For zein protein, which is ∼70% bioavailable, the impact of unabsorbed free AAs on bioavailability was on average 2.3 ± 1.2%-unit in humans and 3.5 ± 5.1%-unit in pigs. In both species, the biggest impact was seen for the free essential AA threonine; its potential absorption could increase threonine bioavailability of zein by 6.6 ± 4.0%-units for humans and 6.6 ± 8.6%-units for pigs. Moreover, for both species the proportion of threonine in free form, relative to total threonine, was significantly higher in ileal digesta after ingestion of zein compared to whey or the protein-free condition (p < 0.05). Conclusions: Our results show that not all free AAs are fully absorbed by the end of the small intestine. When the AA bioavailability of a protein is low, these unabsorbed AAs can be a quantitatively sizable fraction of ingested AAs. Funding Sources: Proteos project, funded by a consortium of food companies and food sectors, coordinated by Global Dairy Platform, USA.